Postharvest Chemical, Sensorial and Physical-Mechanical Properties of Wild Apricot (Prunus armeniaca L.) - MRATINIĆ, Evica; POPOVSKI, Bojan; MILOŠEVIĆ, Tomo; POPOVSKA, Melpomena (University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca, 2011)
Some chemical, sensorial and physical-mechanical properties of 19 apricot genotypes and Hungarian Best (control) such as moisture content, soluble solids content, titratable acidity ratio and their ratio, fruit and stone mass, flesh/stone ratio, fruit dimensions (length, width, thickness), arithmetic and geometric mean diameter, sphericity, surface area and aspect ratio were determined. Their application is also discussed. The highest moisture content and stone mass observed in X-1/1/04 and X-1/2/04, soluble solids content in ZO-1/03, titratable acidity in ZL-2/03, SS/TA ratio in ZL-1/03, and fruit mass and flesh/stone ratio in DL-1/1/04 genotype. The most number of genotypes have orange and deep orange skin and flesh colour, respectively, whereas sweet kernel taste was predominant in most genotypes. Regarding physical-mechanical properties, the superior fruit dimensions (length, width, thickness), arithmetic and geometric mean diameter and surface area observed in DL-1/1/04 genotype, whereas the highest sphericity and surface area observed in X-1/1/04 and X-1/2/04 genotypes. Also, the series of genotypes evaluated have better chemical, sensorial and physical-mechanical properties than Hungarian Best (control). Finally, information about these properties is very important for understanding the behaviour of the product during the postharvest operations.